2013
DOI: 10.1021/mp400313u
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Eye Drops Protect the Retinal Ganglion Cell Layer and Preserve Visual Function in an in Vivo Model of Glaucoma

Abstract: Neuroprotection in glaucoma as a curative strategy complementary to current therapies to lower intraocular pressure (IOP) is highly desirable. This study was designed to investigate neuroprotection by 17β-estradiol (E2) to prevent retinal ganglion cell (RGC) death in a glaucoma model of surgically elevated IOP in rats. We found that daily treatment with E2 containing eye drops resulted in significant E2 concentration in the retina with concomitant profound neuroprotective therapeutic benefits, even in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 60 publications
8
110
0
Order By: Relevance
“…αA-crystallin is a chaperone-like protein involved in remodeling cytoskeleton and preventing protein aggregation, inflammation and apoptosis, and with supposed implications in aging, glaucoma, diabetes, Alzheimer and other neurodegenerative diseases (for review, see [136]). A similar αA-crystallin increase along with retinal protection has been recently detected following treatment with oestradiol drops [137].…”
Section: Oestrogen Retinal Neuroprotectionsupporting
confidence: 75%
“…αA-crystallin is a chaperone-like protein involved in remodeling cytoskeleton and preventing protein aggregation, inflammation and apoptosis, and with supposed implications in aging, glaucoma, diabetes, Alzheimer and other neurodegenerative diseases (for review, see [136]). A similar αA-crystallin increase along with retinal protection has been recently detected following treatment with oestradiol drops [137].…”
Section: Oestrogen Retinal Neuroprotectionsupporting
confidence: 75%
“…9 Next, retinal ganglion cells (the neurons susceptible to glaucomatous damage) express estrogen receptors, and signaling through estrogen receptors may offer cellular protection (also referred to as neuroprotection) for retinal ganglion cells. 88,89 Indeed, the neuroprotective effects of estrogen in the central nervous system are well documented, [90][91][92][93][94][95][96][97][98] and estrogen may offer neuroprotection of axons within the optic nerve as well. Estrogen may also have a protective effect by increasing extracellular matrix production.…”
Section: Endogenous Hormones and Glaucomamentioning
confidence: 99%
“…109 Thus, although it appears to be mild, though statistically significant benefit from the use of HT with estrogen in association with OAG diagnosis, based on the current literature and the USPSTF recommendation, HT should not be used for the purpose of glaucoma prevention or treatment. Interestingly, topical 17-beta-estradiol eye drops have been shown to enhance retinal ganglion cell survival in an animal model of glaucoma, 89 and Another form of exogenous HT in pre-menopausal women is the use of OCs. The Nurses' Health Study followed 79,440 women aged 40 years or older from 1980 to 2006, who were free of OAG at baseline.…”
Section: Exogenous Hormones and Glaucomamentioning
confidence: 99%
“…Therefore, agents that effectively enhance glutamate transporter function may serve as potential therapeutics against the pressure-induced injury. Enhancement of glutamate transport is developing into a new strategy for reducing excitotoxicity also in brain injury and neurodegenerative disease [69][70][71]. Lee et al (2009) [72] reported that tamoxifen, estrogen modulator, possessed neuroprotective properties against excitotoxicity by the up-regulation of GLAST at protein and mRNA levels in the mannganeseinduced excitotoxicity.…”
Section: Neuroprotection By Upregulation Of Glutamate Transportersmentioning
confidence: 99%